Analysis of warrior club rembang's anxiety level facing the djarum 2024 audition matches - Abdurrouf, Mochammad Iqbal; Isna N W, Muhamad; Slamet P, Dani (Universitas Suryakancana, 2024)
The purpose of this study was to analyze the anxiety level of PB Warrior players when participating in the 2024 Djarum Audition. The quantitative descriptive method used in this research is a survey or questionnaire that contains responses to questions from researchers. The subjects of this study were all PB Warrior athletes totaling 25 athletes consisting of 17 boys and 8 girls. While the sample is 5 players, 2 boys and 3 girls who auditioned. The validity of measuring instruments in this study uses professional judgment review, namely the assessment of tools by being guided by people who are competent and experts in their fields, namely coaches, bk teachers and supervisors. The data were analyzed quantitatively with the help of descriptive statistical analysis. The instrument was tested for the validity of the instrument itself. After obtaining a valid instrument, it is used to obtain data directly in the field or on research subjects. Based on the data above, it is known that 0% of athletes are in the very low anxiety category, 40% in the low category, 40% in the medium category, 0% in the high category and 20% in the very high category. Based on this data, there are 4 players who are in the medium to very high category with a percentage of 80%. So it can be said that athletes have a low anxiety category